LAJU DEKOMPOSISI SERASAH DAUN Rhizophora mucronata DAN KONTRIBUSINYA TERHADAP NUTRISI DI PERAIRAN PANTAI SERAMBI DELI KECAMATAN PANTAI LABU - Albino Panjaitan; Yunasfi Djayus; Tajuddin Siregar (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
The mangrove litter which has been decomposed contributes organicmatter as food source for many species of fish and other organisms in themangrove ecosystem. The purpose of this research is to know the decompositionrate of R. mucronata litter leaf and to know the nutrient content of carbon (C),nitrogen (N) and phosphorus (P) in the R. mucronata litter leaf which beenreleased during the decomposition time. This research was done at Serambi DeliBeach Deli Serdang Regency, North Sumatra Province during July untilNovember 2014. This research used purposive sampling method at three stationsand the determination of the station is done by seeing the availability of R.mucronata at the Serambi Deli Beach. The results showed that the decompositionrate of R. mucronata litter leaf on day 105 are 6,41 in stasiun I, 3,56 in station IIand 5,35 in station III. The fastest decomposition rate is the station I with 6,41and the slowest decomposition rate is the station II with 3,56. The nutrient ofcarbon during decomposition in 105 days are 23,48% at station I, 21,96% atstation II and 28,4% at station III. Nutrient of nitrogen which been decomposedon day 105 are 0,42% in station I, 0,7% in station II and 0,54% in station III.Nutrient of phosphorus during decomposition in 105 days are 0,20% in station I,0,22% in station II and 0,23% in station III.Keywords : Serambi Deli Beach, Decomposition, Rhizophora mucronata